Infantile Haemangioma - An unusual location - Yugandar Inakanti; Thimmasarthi Venkata Narsimha Rao (Our Dermatology Online, 2015)
Infantile haemangiomas (IH) are benign vascular neoplasms that have a characteristic clinical course marked by early proliferation and followed by spontaneous involution. Haemangiomas are the most common tumours of infancy and usually are medically insignificant. Cutaneous haemangiomas at particular sites is more common at Head and neck followed by Trunk and Extremities. Extra cutaneous haemangiomas were more common in Liver, Gastrointestinal tract, Larynx, Central nervous system, Pancreas and Lungs. We represent an 8-month-old boy presented with a small but growing, strawberry-colour tumour over the right groin since birth.